ISLAMIC MORAL LIFE AND THREATS TO IT - Mohsen Javadi (Sekolah Tinggi Agama Islam Sadra, 2014)
Islam comprehends the concept of moral life in the term of cultivate of soul to be eligible for drawing near to the transcendent reality, Allah. For that aim, instead of understanding self-realization as permission to submit to one’s appetites, as commonly accepted in modern world, Islam considers self-realization as fruit of self-control by transcending his actual desires and improving his will to make a harmony between psychial aspect (soul)–that covers emotional (heart) and theoretical (reason) activity— and physical aspect (body) –i.e. practical activity (action). The required state of both aspect are formulated in the term “faith” (īmān) and “righteous deeds” (‘amal Ṣālih).